1980
DOI: 10.1055/s-2008-1074981
|View full text |Cite
|
Sign up to set email alerts
|

Indole Alkaloids of Ailanthus altissima

Abstract: From the root bark of Ailanthus altissima four simple indole alkaloids have been isolated: Cathin-6-one (I), 1-methoxy-cathin-6-one (11), Methyl 6-methoxy-P-carboline-I-carboxylate (111) and an unidentified alkaloid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…malabarica (wood) Aono et al (1994), Said et al (2006), Ohmoto et al (1976Ohmoto et al ( , 1981, Varga et al (1980), Souleles and Waigh (1984), Cordell et al (1978) and Koike and Ohmoto (1985) 17…”
Section: Chemical Constituentsmentioning
confidence: 92%
See 2 more Smart Citations
“…malabarica (wood) Aono et al (1994), Said et al (2006), Ohmoto et al (1976Ohmoto et al ( , 1981, Varga et al (1980), Souleles and Waigh (1984), Cordell et al (1978) and Koike and Ohmoto (1985) 17…”
Section: Chemical Constituentsmentioning
confidence: 92%
“…Most of the alkaloids have basic b-Carboline skeleton like Skeleton-I (1-15), six (16-21) may be represented by Canthin-6-one skeleton (Skeleton-II), two (22, 23) by Canthin-6-one-3 N-oxide skeleton (Skeleton-III) and residual two (24 and 25) have individual structures. Aono et al (1994), Ohmoto et al (1981), Joshi et al (1977) and Ohmoto and Koike (1983) 3 b-Carboline-1-propionic acid A. altissima (root bark), A. malbarica (wood) Aono et al (1994) and Ohmoto and Koike (1984) 4 Methyl-4-methoxy-b-caboline carboxylate A. altissima (root bark) Varga et al (1980) …”
Section: Chemical Constituentsmentioning
confidence: 98%
See 1 more Smart Citation
“…(Simaroubaceae) is used in Chinese traditional medicine as a bitter-aromatic drug, in the treatment of cold and gastric diseases and as an antitumoral. Previous phytochemical studies have demonstrated the presence in the plant of quassinoids (Casinovi et al, 1983;Chiarlo and Pinca, 1965;Kubota et al, 1996;Lu et al, 2002;Niimi et al, 1987) as well as indole and β-carboline alkaloids (Ohmoto et al, 1981;Ohmoto and Koike, 1984;Souleles and Kokkalou, 1989;Varga et al, 1981).…”
Section: Introductionmentioning
confidence: 97%
“…Swingle, Simaroubaceae, is a large tree («Tree of Heaven») distributed from Southeast Asia to China and Taiwan, but is also grown in cities in Europe and North America. It is employed as an antibacterial, anthelmintic, amoebicide, and insecticide [1][2][3]. Its biological activities depend mainly on quassinoids as well as on indole alkaloids, either the simple β-carbolines or the canthin-6-ones [4,5].…”
mentioning
confidence: 99%